THE IMPACT OF ARTIFICIAL INTELLIGENCE IN INDIA. (International Journal of Food and Nutritional Sciences, 2022)
AI is regarding artificial life-forms that can improve on human intelligence, and for others, almost any data processing technology can be called AI. Artificial intelligence (AI) has been applied widely in our daily lives in a variety of ways with numerous successful stories. Examine in AI has built upon the tools and techniques of numerous in different disciplines; the application of various disciplines in AI has necessitated the development of many enhancements and extensions. AI has also contributed to dealing with the corona virus disease (COVID-19) pandemic, which is currently. In addition to helping us develop our bodies, AI technology is also accepted to help us create artificial life forms. Science fiction has long recommended the concept of human-like robots that are capable of difficult interactions. It Cause of Unemployment Artificial Intelligence has dramatically improved our world in ways unimaginable, but there are many concerns regarding the impact it can have on employment and the credibility of the workforce. There are predictions that tell us about the possibility of millions of people facing unemployment in the next decade due to automation and neural networks. There has been a significant transformation in business, education, banking, and the market and government sector due to AI. This can inform the development of more detailed models of safety assurance and contribute to more effective risk control.